„… prawda musi wybrać połowę paradoksu i połowę stereotypu”. O tajemnicach Żyda wiecznego tułacza Aleksandra Wata - Tomassucci , Giovanna (Przestrzenie Teorii, 2023)
Aleksander Wat’s novella The Wandering Jew, published in 1926, is his only prose text in which the Jewish motif is the very center of the narrative. Wat carefully avoids dramatic or frightening notes, staying away from the characters created by Potocki, Quinet, Schubart, and Meyrink. However, certain aspects of the old version of the ancient myth remain: the millennial peregrination through history, the absolute solitude of the hero, and his magical movement and appearance in different parts of the world. The fusion of Catholicism and communism in the shadow of Marranism, represented by the protagonist Nathan, reflects grotesquely either on the phenomenon of Jewish youth fleeing the shtetls observed by young Wat, or on his own ecumenical dreams and reflections on the metahistorical role of Jews and their conversion. The article analyzes this issue also with particular regard either to the reception of the old Christian legend, or to the Anti-semitic narrative on the conspiracy of Jewish converts, shared by Keith Gilbert Chesterton, a contemporary writer very important for Wat.